The Effect of NaOH Concentration on The Physical and Chemical Properties of Jerbung Shrimp (Fenneropenaeus Merguiensis de Man) Waste Powder: Jerbung Shrimp (Fenneropenaeus Merguiensis de Man) Waste Powder - Satria, Wiranto; Nazarudin, Nazarudin; Mursalin, Mursalin (Jurnal Bio-Geo Material Dan Energi, 2024)
This research was conducted to determine the effect of NaOH concentration on the physical and chemical properties of shrimp waste powder. This research used a Completely Randomized Design (CRD) with NaOH concentration treatment consisting of 5 levels (1%, 1.25%, 1.5%, 1.75% and 2%) and 4 repitition. The data obtained were analyzed statistically using analysis of variance and followed by Duncan's New Multiple Range Test (DnMRT) when necessary. The research shows that the NaOH concentration has a significant effect on the ash content, protein content, L* and b* values, but has no significant effect on the water content, fat content, solubility and a* values. The best characteristics of shrimp waste powder is obtained using NaOH 1.5% which produces powder with 4.22% water, 39.27% ash, 18.37% protein, 12.43% fat, solubility of 4. 04%, L* value 48.37, a* value 10.92 and b* value 21.47.